Assessment of corneal epithelial thickness mapping by spectral-domain optical coherence tomography - Tañá-Rivero, Pedro; Orts-Vila, Paz; Tañá-Sanz, Pedro; Ramos-Alzamora, María; Montés-Micó, Robert (Frontiers in Medicine, 2024)
To assess corneal epithelial-thickness (ET) mapping resulting from spectral-domain-optical-coherence-tomography (SD-OCT) by analysing its repeatability and reproducibility and its utility for screening corneal-refractive-surgery (CRS) candidates. METHODS: ET was measured in 25-sectors by two-operators. Intra-subject-standarddeviation, coefficient-of-repeatability (CoR) and coefficient-of-variability (CoV) were calculated to evaluate repeatability. Reproducibility was evaluated using a Bland-Altman analysis. Scheimpflug-tomography, refraction, visual acuity, and patient history were used to make a decision on eligibility for CRS. After this decision, the surgeon was shown the patient's ET map and was asked to reconsider his analysis. The percentage of screenings that changed after evaluating the ET maps was determined. RESULTS: 43 eyes with normal corneas (CRS-group) and 21 eyes not suitable for CRS (non-CRS-group) were studied. For the CRS-group, CoR ranged from 2.03 (central) to 19.73μm (outer-inferonasal), with the central-sector showing the highest repeatability (CoV:1.53-1.80%). For the non-CRS-group, CoR ranged from 3.82 (central-middle-superonasal) to 13.42μm (middle-inferotemporal), with the inner-superonasal-sector showing the highest repeatability (CoV:2.86-4.46%). There was no statistically significant difference between operators (P>0.01). In the CRS-group, the outcomes showed a narrow 95% limits-of-agreement (LoA) for the central-and inner-nasal-sectors (about 4μm), and wider for the inner-superior, outer-superotemporal and outer-inferonasal (about 10-14μm). In the non-CRS-group, they were for the outer superonasal (about 4μm), and for the middle-inferotemporal and outer-temporal (about 10μm), respectively. Candidacy for CRS changed in 7.82% of patients after evaluation of the ET maps, with all of them screened-out. CONCLUSIONS: The SD-OCT provided repeatable and reproducible corneal ET measurements and may alter candidacy for CRS.